BRAINSTORMING TECHNIQUE TO DEVELOP THE STUDENTSâ€™ WRITING SKILL - Nita Nurlaela Sa'ban; Wahid Hasim (Institut Pendidikan Indonesia Garut, 2019)
The aim of this study entitled â€œBrainstorming Technique to Develop the Studentsâ€™ Writing Skillâ€ was to investigate to find out the effectiveness of brainstorming technique in teaching writing. The research was conducted to 35 students in the 2nd grade at SMP N 1 Tarogong Kidul. The data was collecting on 19 April 2016 until 17 May 2016. The researcher used a quantitative method to answer this problem. First, the students were given pre-test to know the ability studentsâ€™ writing before giving treatment. Then, the students were given the treatment by teaching writing using brainstorming technique. After giving the treatment, the studentsâ€™ was given a post-test. The result of pre-test and post-test were analyzed by using t-test. All the processes of collecting, analyzing and interpreting the data were aimed to test the hypothesis. The researcher used the hypothesis criterion test if:-tcritical â‰¤ tobserved â‰¥ tcritical, then alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It means that there is significant difference of using brainstorming in studentsâ€™ writing skill as the tobserved pointed at 11.884, and tcritical pointed 2.0484, so the tobserved (11.884) was higher than -tcritical (- 2.0484) and tcritical (2.0484). The research resulted, alternative (Ha) was accepted and null hypothesis (Ho) was rejected. Moreover, it means that there was difference of using brainstorming in studentsâ€™ writing skill.